DCM boost interleaved converter for operation in AC and DC to trolleybus application - Canesin, Carlos A. [UNESP] (2009)
This paper is based on the development and experimental analysis of a DCM Boost interleaved converter suitable for application in traction systems of electrical vehicles pulled by electrical motors (Trolleybus), which are powered by urban DC or AC distribution networks. This front-end structure is capable of providing significant improvements in trolleybuses systems and in the urban distribution network costs, and efficiency. The architecture of proposed converter is composed by five boost power cells in interleaving connection, operating in discontinuous conduction mode. Furthermore, the converter can operate as AC-DC converter, or as DC-DC converter providing the proper DC output voltage range required by DC or AC adjustable speed drivers. Therefore, when supplied by singlephase AC distribution networks, and operating as AC-DC converter, it is capable to provide high power factor, reduced harmonic distortion in the input current, complying with the restrictions imposed by the IEC 61000-3-4 standards. The digital controller has been implemented using a low cost FPGA and developed totally using a hardware description language VHDL and fixed point arithmetic. Thus, two control strategies are evaluated considering the compliance with input current restrictions imposed by IEC 61000-3-4 standards, the regular PWM modulation and a current correction PWM modulation. In order to verify the feasibility and performance of the proposed system, experimental results from a 15 kW low power scale prototype are presented, operating in DC and AC conditions.